The level of Emotional Intelligence and its Relationship to the Strategies of Tackling the Teaching Stress among teachers in the first cycle of basic education - Afield Study in Lattakia city (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The aim of the research is to identify the level of Emotional Intelligence and Strategies of Tackling the Teaching Stress among teachers in the first cycle of basic education in Lattakia city, and to identify the relationship between the level of Emotional Intelligence and Strategies of Tackling the Teaching Stress among the sample of teachers, as well as the difference between teachers in the level of Emotional Intelligence and Strategies of Tackling the Teaching Stress among the sample of teachers according to (gender, years of experience). In order to achieve the objective of the research, the descriptive analytical method was used. The sample included (268) teachers for the academic year 2018/2019. Two measures were applied. The first (Emotional Intelligence), included (46) clauses, and the second, (Strategies of Tackling the Teaching Stress) included (30) clauses.Reached several results, the most important of them:-     The level low of Emotional Intelligence came with percent of (47.8%), and the level high of Emotional Intelligence came with percent of (49.3%) of the research sample.-     The important Strategies of Tackling the Teaching Stress of the research sample sociality Strategies, then, Psychological Strategies corporality).-     A positive vulnerable correlation between the Strategies of Tackling the Teaching Stress  and the level low of Emotional Intelligence, also A positive strong correlation between the Strategies of Tackling the Teaching Stress  and the level high of Emotional Intelligence among teachers in the first cycle of basic education in Lattakia city.-     There were no statistically significant differences among the sample in the level of Emotional Intelligence and Strategies of Tackling the Teaching Stress according to gender.-     There were statistically significant differences among the sample of teachers in the level of Emotional Intelligence in favor of more than (10) years, and Whereas there are no differences in the Strategies of Tackling the Teaching Stress according to years of experience.